The Oxford Book of Legal Anecdotes - Gilbert, Michael Francis, 1912-2006. (Oxford : Oxford University Press, 1989)
An anthology of over 350 anecdotes about legal goings-on in Britain, the States, and Australia that will intrigue and entertain almost everyone.
Originally published: 1986.
Includes index.
Keywords: Law -- History and criticism -- Periodicals